Popular press portrayal of issues surrounding free‐roaming domestic cats Felis catus. Issue 1 (20th October 2021) - Gow, Elizabeth A.; Burant, Joseph B.; Sutton, Alex O.; Freeman, Nikole E.; Grahame, Elora R. M.; Fuirst, Matthew; Sorensen, Marjorie C.; Knight, Samantha M.; Clyde, Hannah E.; Quarrell, Nathaniel J.; Wilcox, Alana A. E.; Chicalo, Roxan; et al.
Abstract: Domestic cats Felis catus have a complex and contentious history. They fill multiple societal roles (e.g. as pest controllers and companion animals), which has led to a variety of animal welfare, conservation, and human health concerns. Popular press articles play an important role in how people learn about key issues surrounding cats, but they may present some issues more frequently than other issues. We conducted a global media content analysis of 796 articles in the English‐language media from 1990 to 2018 on issues related to free‐roaming cats, such as their environmental impacts, the threats and welfare issues cats face, and how they are managed. We aimed to determine whether non‐experts learning about the issues around free‐roaming cats exclusively from the popular press would be exposed to multiple stakeholder views or opinions. Over 95% of articles analysed were from North America. Most of the people interviewed in the popular press were from non‐governmental organizations, mainly from cat welfare or cat rights groups (which are often focused on only one side of the issue). Researchers, shelter organizations, veterinarians, and groups that have different opinions than cat rights or welfare organizations on how to resolve issues surrounding free‐roaming cats were rarely interviewed by the popular press. Most articles focused on cat welfare issues and the management strategies of euthanasia or trap–neuter–release (TNR), whereas less than one‐third of the articles acknowledged that cats have any impact on wildlife or the broader environment. We found that the popular press often presented an oversimplified picture of issues related to free‐roaming cats and provided unbalanced coverage. We also show evidence of framing by the popular press, including mainly presenting the viewpoints and perspectives from animal welfare and rights groups, focusing on TNR or euthanasia as the only viable cat management strategies when many alternatives exist and often have greater support from experts, and discussing the impacts of cats on birds and small mammals but not reptiles or amphibians. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.